Beliefs of Australian physical therapists related to lumbopelvic pain following a biopsychosocial workshop - Beales, Darren; O'Sullivan, Peter (Education Section, American Physical Therapy Association, 2014)
Introduction. The purpose of this study was to determine if participation in a 1-day workshop focusing on the biopsychosocial nature of lumbopelvic pain disorders would influence the beliefs of physical therapists in Australia. Review of the Literature. Within the biopsychosocial model of pain disorders,there is growing understanding of the role of beliefs as a potential contributor to disability.Not only is there an interest in the beliefs of those afflicted with pain disorders, but also in the beliefs of the health care practitioner (HCP). HCP beliefs have the potential to influence management and client beliefs in both positive and negative ways.Subjects. Physical therapists who voluntarily attended a 1-day professional development workshop in Australia (n = 77).Methods. Physical therapist beliefs related to back pain (modified Back Beliefs Questionnaire) and pelvic girdle pain (customized questions) were assessed pre- and post-workshop. The title of the workshop was “A contemporary biopsychosocial approach to pelvic girdle pain.” The content included presentation of contemporary scientific evidence, case study examples, and live patient demonstrations.Results. Beliefs related to lumbopelvic pain demonstrated a positive shift following the participation in the workshop (ANOVA P = .03). For pelvic girdle pain, there was a shift in beliefs related to thecauses that is more aligned with current literature in this area (ANOVA P < .01).Discussion and Conclusion. A 1-day professional development workshop resulted in more positive beliefs related to lumbopelvic pain in Australian physical therapists. Further research is required toidentify key education strategies to change beliefs that have a positive flow on effect to altering HCP behaviors.